Ready for retirement? - Tiffany, Gordon (American City & County, 2006)
This article focuses on the transition of Baby Boomers to full-time retirement made on their own terms. The majority of today's workers are redefining retirement, with many of them seeing it as a series of new challenges. As more members of the Boomer generation become eligible for retirement, employers inevitably will recognize the need to retain or attract experienced and mature workers. Flexible work arrangements that meet the needs of employers and retirement phasers will become standard practices.